The sentence repetition task as a measure of sign language proficiency - Schönström, Krister; Hauser, Peter C. (Applied psycholinguistics, 2022)
Sign language research is important for our understanding of languages in general and for the impact it has on policy and on the lives of deaf people. There is a need for a sign language proficiency measure, to use as a grouping or continuous variable, both in psycholinguistics and in other sign language research. This article describes the development of a Swedish Sign Language Sentence Repetition Test (STS-SRT) and the evidence that supports the validity of the test’s interpretation and use. The STS-SRT was administered to 44 deaf adults and children, and was shown to have excellent internal reliability (Cronbach’s alpha of 0.915) and inter-rater reliability (Intraclass Correlation Coefficient [ICC] = 0.900, p < .001). A linear mixed model analysis revealed that adults scored 20.2% higher than children, and delayed sign language acquisition were associated with lower scores. As the sign span of sentences increased, participants relied on their implicit linguistic knowledge to scaffold their sentence repetitions beyond rote memory. The results provide reliability and validity evidence to support the use of STS-SRT in research as a measure of STS proficiency.